Peran Kepemimpinan Inklusif terhadap Kinerja Tim Organisasi Mahasiswa di STIE Mahardhika Surabaya - Agus Wahyudi; Muhamad Dannil; Andini Cahya Dwi Malini; Dela Arianti; Siti Asih Dwi Anggraeni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
During the globalization age, culturally and ethnically diverse organizations are increasing. To overcome differences and create a harmonious and productive work environment, inclusive leadership is essential. In student organizations, leadership plays an important role in producing effective teams. In the context of the diversity of student organization members of STIE Mahardhika Surabaya, this study attempts to explain how inclusive leadership practices affect team performance. This study conducted a descriptive qualitative study involving observation, documentation, and in-depth interviews and research on two student organizations, UKM Jurnalistik and PMII. The study showed that an open inclusive leadership style in UKM Jurnalistik was able to increase two-way communication, member participation, and a sense of belonging to the organization, which had a positive impact on team performance. Meanwhile, a more structural but still inclusive leadership style in PMII was also able to increase two-way communication, member participation, and a sense of belonging to the organization.